Difference and discrimination of infrared spectral properties of sauce-flavor Baijiu with different processes - WU Deguang, ZHANG Wenjuan, LU Jun, WANG Fan, FENG Haiyan, XIA Ya, TANG Ping, LI Changwen (Zhongguo niangzao)
In order to prevent the chaos of shoddy sauce-flavor (Jiangxiangxing) Baijiu market, realize the rapid identification of Baijiu technology, the infrared spectra of dry matter of Baijiu with 4 kinds of processes including Kunsha, Suisha, Fansha and Chuansha were collected, and the characteristics of one-dimensional spectrum and second-order derivative spectrum were investigated. With temperature as the external disturbance, the synchronous and asynchronous two-dimensional correlation spectra of each process Baijiu were constructed. In addition, the infrared spectrum of the liquor body was collected, and the discriminant model of traditional Daqu sauce-flavor Baijiu and reusing distiller's grain Baijiu was established by partial least square method. The dry matter of sauce-flavor Baijiu with different processes showed obvious characteristics in infrared spectrum, and the characteristic peak near 1 737 cm-1 was the main difference between traditional Daqu sauce-flavor Baijiu and reusing distiller's grain Baijiu. Under the temperature perturbation, sauce-flavor Baijiu with different processes showed different sensitivity and intermolecular interaction in the two-dimensional correlation infrared spectrum. The partial least squares-discriminant model based on the infrared spectrum of liquor body was established. The calibration set R2Cal was 0.996 5, the root mean square error of calibration (RMSEC) was 0.057 1, the cross-validation set R2Val was 0.966 2, and the root mean square error of cross validation(RMSECV) was 0.190 2. There were obvious characteristics in the infrared spectral properties of sauce-flavor Baijiu with different processes. The process discrimination model based on infrared spectrum technology could effectively distinguish the process of sauce-flavor Baijiu.